2013
DOI: 10.1590/s1984-29612013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Hematological changes in Eleginops maclovinus during an experimental Caligus rogercresseyi infestation

Abstract: Eleginops maclovinus has been an important fishery resource in Chile since 1957. Caligus rogercresseyi is one of the most prevalent ectoparasite species found on E. maclovinus. Hematocrit, hemoglobin level, red blood cell count (RBC), white blood cell count (WBC), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and differential white blood cell count were determined before and after an experimental infestation with C. rogercresseyi. We found si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…RBC parameters can be the fastest way to detect stress and blood loss caused by parasitic infestation in a fish population (Nair & Nair 1983, Fajer-Ávila et al 2011, Peña-Rehbein et al 2013, Ranzani-Paiva et al 2013). Thus, hematological evaluations have become a routine practice for assessing the health of a fish population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RBC parameters can be the fastest way to detect stress and blood loss caused by parasitic infestation in a fish population (Nair & Nair 1983, Fajer-Ávila et al 2011, Peña-Rehbein et al 2013, Ranzani-Paiva et al 2013). Thus, hematological evaluations have become a routine practice for assessing the health of a fish population.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, even at a moderate level of infestation, L. cyprinacea was able to induce a decrease in the condition factor of A. altiparanae, suggesting that in the case of this fish species, the effects of the parasitism may be more related to the size of the fish than the intensity of the infestation. In contrast, other studies have reported that the abundance of crustacean parasites per fish was not high enough to cause a reduction in the condition factor despite the gill injuries observed (Fajer-Ávila et al 2011).RBC parameters can be the fastest way to detect stress and blood loss caused by parasitic infestation in a fish population (Nair & Nair 1983, Fajer-Ávila et al 2011, Peña-Rehbein et al 2013, Ranzani-Paiva et al 2013). Thus, hematological evaluations have become a routine practice for assessing the health of a fish population.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…(Shimura et al, 1983;Ranzani-Paiva et al, 1987;Ruane et al, 1999;Tavares-Dias et al, 1999;Haond et al, 2003), Ichthyophthirius multifiliis (Tavares-Dias et al, 2002), Argulus sp., I. multifilis and Dactylogyrus vastator (Küçükgül Güleç and Şahan, 2010), Henneguya branchialis (Sabri et al, 2009), Caligus rogercresseyi (Peña-Rehbein et al, 2013), Dolops carvalhoi , Dactylogyridae, Urocleidoides ermitus, Anacanthorus sp., (Correa et al, 2013), Clinostomum complanatum (Kaur et al, 2012), Trachelobdella lubrica (Çelik and Aydın, 2006), Monogenea, Protozoa, Crustacea (El-Seify et al, 2011), Anacanthorus penilabitus, Piscinoodinium pillulare, I. multifiliis, P. pillulare (Tavares-Dias et al, 2008) can influence blood parameters in different host fish. Only one study which investigates the impact of C. oestroides on the blood parameters of the fish is available.…”
mentioning
confidence: 99%